2019
DOI: 10.15421/011924
|View full text |Cite
|
Sign up to set email alerts
|

Influence of essential oils of plants on the migration activity of Tribolium confusum (Coleoptera, Tenebrionidae)

Abstract: Pest control should be ecologically-based, therefore use of ecologically safe approaches is the best variant. Essential oils of plants can affect the main metabolic, biochemical, physiological and behavioural functions of insects. In the experiment, we evaluated the influence of 20 essential oils on migration activity of imagoes of Tribolium confusum Jacquelin du Val, 1863 in the conditions of a laboratory experiment. Notable repellent activity against T. confusum was exhibited by essential oils of Jasminum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…For example, Opatrum sabulosum (Linnaeus, 1761), a dangerous pest in Steppe and Forest-Steppe zone of Eurasia, cannot consume plants of certain species (Brygadyrenko & Nazimov, 2014. Volatile compounds present in some species of plants can scare off or lure insects (Martynov et al, 2019). Plant remains on the soil surface change horizontal structure of communities of invertebrates (Faly & Brygadyrenko, 2014), which can occur directly during consumption of food, as well as indirectly by changes in species composition of biocenosis in certain parts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Opatrum sabulosum (Linnaeus, 1761), a dangerous pest in Steppe and Forest-Steppe zone of Eurasia, cannot consume plants of certain species (Brygadyrenko & Nazimov, 2014. Volatile compounds present in some species of plants can scare off or lure insects (Martynov et al, 2019). Plant remains on the soil surface change horizontal structure of communities of invertebrates (Faly & Brygadyrenko, 2014), which can occur directly during consumption of food, as well as indirectly by changes in species composition of biocenosis in certain parts.…”
Section: Discussionmentioning
confidence: 99%
“…Over the recent 50 years, control of pests in agriculture has been based on use of synthetic chemical insecticides in field agrocenoses and conditions of greenhouse cultivation. However, synthetic insecticides are toxic, they cause a non-favourable impact on the environment, polluting soil, water and air, and also their large scale use leads to development of resistance in the target species and significant damage to populations of non-target species of invertebrates (Benhalima et al, 2004;Pimentel et al, 2009;Boyko & Brygadyrenko, 2017;Martynov & Brygadyrenko, 2017, 2018Martynov et al, 2019). Strict measures of ecological regulation of use of pesticides have led to growth of a number of studies on use of natural plant extracts as an alternative to synthetic preparations (Isman, 2004;Pérez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of monoterpenoids, sesquiterpenes, and alcohols have been proven to be attributes of the repellent properties of essential oils (Sritabutra & Soonwera, 2013;Sathantriphop et al, 2015Martynov et al, 2019. Taylor et al (2012) and Dickens & Bohbot (2013) showed that the odorant receptor neuron in a mosquito's antennal sensilla is activated by linalool, a naturally occurring terpene alcohol and by eucalyptol, a natural organic compound.…”
Section: Discussionmentioning
confidence: 99%